A kind of sludge-based pressure-resistant permeable brick and preparation method thereof

By using sludge and steel slag as raw materials, calcined modified bentonite, combined with segmented calcination treatment, permeable bricks with excellent permeability and compressive resistance are prepared, which solves the problem of insufficient compressive resistance of existing permeable bricks and achieves a higher service life and performance.

CN119774980AInactive Publication Date: 2025-04-08ZONGYANG COUNTY HENGSHENG NEW BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411856816.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

While improving the permeable performance of existing permeable bricks, they have insufficient compressive performance, resulting in easy crushing when used on urban roadsides and significantly reducing their service life.

Method used

Sludge and steel slag are used as the main raw materials, and water-permeable bricks with excellent water permeability and compressive resistance are prepared by introducing calcined modified bentonite and combined with segmented calcination treatment.

Benefits of technology

The permeable bricks are achieved while ensuring high permeability performance, and significantly improving the compressive strength, avoiding the problem of crushing the permeable bricks during use and extending the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005192053420000121
    Figure BDA0005192053420000121
  • Figure BDA0005192053420000131
    Figure BDA0005192053420000131
Patent Text Reader

Abstract

The invention relates to the technical field of permeable bricks, and discloses a sludge-based pressure-resistant permeable brick and a preparation method thereof. The brick comprises the following components: steel slag, sludge, potassium feldspar, calcined modified bentonite, fly ash and perlite powder; the weight ratio of the sludge to the calcined modified bentonite is 20:1; the calcined modified bentonite is prepared by modifying calcium-based bentonite as a raw material. The permeable brick prepared by using steel slag and sludge as raw materials not only has excellent water permeability, but also has excellent pressure resistance. The brick is applied to urban roadside paving and can withstand greater pressure. At the same time, the brick can timely penetrate rainwater on the roadside, so that the city is free from the trouble of waterlogging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of permeable bricks, in particular to a sludge-based pressure-resistant permeable brick and a preparation method thereof. Background Art

[0002] In cities with more rain, urban waterlogging disasters are usually more serious. Therefore, building a water-absorbing "sponge city" can absorb water, store water, and infiltrate water when it rains, thereby greatly reducing the damage caused by urban waterlogging. Based on this, permeable bricks have been widely favored due to their unique performance.

[0003] Permeable bricks are the basic materials needed to build sponge cities. By laying permeable bricks with good permeability, it can effectively reduce urban surface runoff, alleviate urban waterlogging, and reduce the heat island effect. Therefore, permeable bricks will consume a lot of raw materials.

[0004] In order to deal with the endogenous pollution caused by the bottom mud of water bodies, the current treatment method is usually excavation and dredging, which produces a large amount of sludge. If it is used as a resource, it can protect the environment and save resources. Therefore, the present invention uses sludge as one of the raw materials for the preparation of permeable bricks. This not only improves the utilization rate of sludge, but also greatly reduces the purchase and consumption of other raw materials, which is of great significance to ecological protection, resource conservation and sustainable development.

[0005] Based on this, we proposed a sludge-based pressure-resistant permeable brick, hoping to solve the shortcomings of the existing technology. Summary of the invention

[0006] 1. Technical issues to be solved

[0007] In view of the deficiencies in the prior art, the present invention provides a sludge-based pressure-resistant permeable brick and a preparation method thereof.

[0008] (II) Technical solution

[0009] To achieve the above-mentioned purpose, the present invention provides the following technical solutions:

[0010] A sludge-based pressure-resistant permeable brick, comprising the following components by weight: 30-38 parts of steel slag, 20-60 parts of sludge, 10-20 parts of potassium feldspar, 1-3 parts of calcined modified bentonite, 3-5 parts of fly ash, and 1-2 parts of perlite powder;

[0011] The weight ratio of the sludge to the calcined modified bentonite is 20:1;

[0012] The calcined modified bentonite is prepared by modifying calcium-based bentonite as a raw material.

[0013] As a further technical solution, the method for preparing calcined modified bentonite comprises the following steps:

[0014] (1) First, the calcium-based bentonite is piled up, and then the sodium hydroxide solution is evenly sprayed until the water content of the calcium-based bentonite reaches 40-50%, and then the calcium-based bentonite is piled up at room temperature for 24 hours;

[0015] (2) adding zinc nitrate solution and aluminum nitrate solution into the reaction kettle in sequence, stirring for 30 minutes in a water bath, and then adding sodium hydroxide and sodium bicarbonate mixed solutions respectively, adjusting the pH of the system to 11.3, continuing to stir for 4 hours, standing for 20 hours, and then filtering, washing with clean water until neutral, drying, and crushing to obtain a mixed modified material;

[0016] The drying temperature is 60°C and the drying time is 1 hour;

[0017] (3) adding the mixed modified material to the stacked calcium-based bentonite, mixing evenly, and obtaining a standby material;

[0018] (4) Then, the prepared material is placed in a resistance furnace and subjected to a staged calcination treatment to obtain calcined bentonite.

[0019] As a further technical solution, the concentration of the sodium hydroxide solution in step (1) is 0.2 mol / L.

[0020] As a further technical solution: in step (2), the concentration of the zinc nitrate solution is 1 mol / L;

[0021] The concentration of aluminum nitrate solution is 1.5 mol / L;

[0022] The volume ratio of zinc nitrate solution to aluminum nitrate solution is 1:2;

[0023] The sodium hydroxide concentration in the sodium hydroxide and sodium bicarbonate mixed solution is 0.8 mol / L, and the sodium bicarbonate concentration is 1.5 mol / L.

[0024] As a further technical solution: in step (3), the mixed modified material and calcium-based bentonite are mixed in a mass ratio of 1-3:20.

[0025] As a further technical solution, the staged calcination treatment in step (4) is as follows:

[0026] First, calcine at 300°C for 15 minutes, then adjust the temperature to 420°C, and continue calcining for 20 minutes to complete the entire calcination process.

[0027] As a further technical solution, the staged calcination treatment is carried out in an air atmosphere.

[0028] As a further technical solution: the heating rate of the staged calcination treatment is 5°C / s.

[0029] A method for preparing sludge-based pressure-resistant permeable bricks, comprising:

[0030] (1) Weighing the raw materials of each component according to their weight parts: steel slag, sludge, potassium feldspar, calcined modified bentonite, fly ash, and perlite powder;

[0031] (2) adding each raw material component into a mixer in sequence, and then adding 10% of water to the total amount of the raw materials, continuing to stir, and sealing and aging for 20 hours to obtain an aged material;

[0032] (3) injecting the aged material into a mold, pressing it into a brick at a pressure of 22-24 MPa, and then drying the brick at 100° C. for 12 hours;

[0033] (4) placing the dried bricks in a furnace and firing them into shape;

[0034] The firing heating rate is 6℃ / min, the temperature is raised to 750℃ and kept for 1h, and then the temperature is further raised to 1110℃ and sintered and kept for 2h, then cooled and discharged.

[0035] (III) Beneficial effects

[0036] Compared with the prior art, the present invention provides a sludge-based pressure-resistant permeable brick, which has the following beneficial effects:

[0037] The permeable bricks made of steel slag and sludge as raw materials of the present invention not only have excellent water permeability, but also have excellent compressive resistance. When applied to urban roadside paving, they can withstand greater pressure and can timely penetrate rainwater on the roadside, thus preventing the city from the trouble of waterlogging.

[0038] Since water permeability and compressive strength are two contradictory performance indicators, when the internal porosity of the permeable brick increases and the water permeability is enhanced, the overall density of the permeable brick will decrease, which will in turn lead to a decrease in compressive strength. Therefore, the present invention introduces calcined modified bentonite, which, in combination with sludge, can greatly ensure the compressive strength of the permeable brick while ensuring the high water permeability of the permeable brick, so that the compressive strength is maintained at a high level, thereby avoiding the situation that the compressive strength is too low when the permeable brick has good water permeability, which makes it easy to be crushed during use, resulting in a significant reduction in service life. The permeable bricks prepared by the present invention obviously avoid this situation.

[0039] At a higher sintering temperature, a certain amount of molten glass phase will be generated in the brick system by calcining modified bentonite, which can promote the migration of crystals under the action of capillary force. The particles in the system will be arranged toward a higher packing density, thereby greatly improving the compressive strength of the sintered brick. However, if the firing process is too long, the continuous pores inside the permeable brick system will begin to transform into isolated pores, causing the permeability of the permeable brick to decrease rapidly. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0041] Example 1

[0042] A method for preparing sludge-based pressure-resistant permeable bricks, comprising:

[0043] (1) Weigh the raw materials of each component according to their weight: 30 parts of steel slag, 20 parts of sludge, 10 parts of potassium feldspar, 1 part of calcined modified bentonite, 3 parts of fly ash, and 1 part of perlite powder;

[0044] The weight ratio of the sludge to the calcined modified bentonite is 20:1;

[0045] The calcined modified bentonite is prepared by modifying calcium-based bentonite as a raw material.

[0046] (2) adding each raw material component into a mixer in sequence, and then adding 10% of water to the total amount of the raw materials, continuing to stir, and sealing and aging for 20 hours to obtain an aged material;

[0047] (3) injecting the aged material into a mold, pressing it into a brick at a pressure of 22 MPa, and then drying the brick at 100° C. for 12 hours;

[0048] (4) placing the dried bricks in a furnace and firing them into shape;

[0049] The firing heating rate is 6℃ / min, the temperature is raised to 750℃ and kept for 1h, and then the temperature is further raised to 1110℃ and sintered and kept for 2h, then cooled and discharged.

[0050] The method for preparing calcined modified bentonite comprises the following steps:

[0051] (1) First, the calcium-based bentonite is piled up, and then the sodium hydroxide solution is evenly sprayed until the water content of the calcium-based bentonite reaches 40%, and then the calcium-based bentonite is piled up at room temperature for 24 hours; the concentration of the sodium hydroxide solution is 0.2 mol / L.

[0052] (2) adding zinc nitrate solution and aluminum nitrate solution into the reaction kettle in sequence, stirring for 30 minutes in a water bath, and then adding sodium hydroxide and sodium bicarbonate mixed solutions respectively, adjusting the pH of the system to 11.3, continuing to stir for 4 hours, standing for 20 hours, and then filtering, washing with clean water until neutral, drying, and crushing to obtain a mixed modified material;

[0053] The drying temperature is 60°C, the drying time is 1 hour, and the concentration of zinc nitrate solution is 1 mol / L;

[0054] The concentration of aluminum nitrate solution is 1.5 mol / L;

[0055] The volume ratio of zinc nitrate solution to aluminum nitrate solution is 1:2;

[0056] The sodium hydroxide concentration in the sodium hydroxide and sodium bicarbonate mixed solution is 0.8 mol / L, and the sodium bicarbonate concentration is 1.5 mol / L.

[0057] (3) adding the mixed modified material to the stacked calcium-based bentonite, mixing evenly, and obtaining a standby material; the mixed modified material and calcium-based bentonite have a mixing mass ratio of 1:20.

[0058] (4) Then, the reserved material is placed in a resistance furnace and subjected to a staged calcination treatment to obtain calcined bentonite; the staged calcination treatment is as follows:

[0059] First, calcine at 300°C for 15 minutes, then adjust the temperature to 420°C, and continue calcining for 20 minutes to complete the entire calcination process; the staged calcination process is carried out in an air atmosphere; the heating rate of the staged calcination process is 5°C / s.

[0060] Example 2

[0061] A method for preparing sludge-based pressure-resistant permeable bricks, comprising:

[0062] (1) Weigh the raw materials of each component according to their weight: 32 parts of steel slag, 40 parts of sludge, 12 parts of potassium feldspar, 2 parts of calcined modified bentonite, 3.5 parts of fly ash, and 1.2 parts of perlite powder;

[0063] The weight ratio of the sludge to the calcined modified bentonite is 20:1;

[0064] The calcined modified bentonite is prepared by modifying calcium-based bentonite as a raw material.

[0065] (2) adding each raw material component into a mixer in sequence, and then adding 10% of water to the total amount of the raw materials, continuing to stir, and sealing and aging for 20 hours to obtain an aged material;

[0066] (3) injecting the aged material into a mold, pressing it into a brick at a pressure of 23 MPa, and then drying the brick at 100° C. for 12 hours;

[0067] (4) placing the dried bricks in a furnace and firing them into shape;

[0068] The firing heating rate is 6℃ / min, the temperature is raised to 750℃ and kept for 1h, and then the temperature is further raised to 1110℃ and sintered and kept for 2h, then cooled and discharged.

[0069] The method for preparing calcined modified bentonite comprises the following steps:

[0070] (1) First, the calcium-based bentonite is piled up, and then the sodium hydroxide solution is evenly sprayed until the water content of the calcium-based bentonite reaches 45%, and then the calcium-based bentonite is piled up at room temperature for 24 hours; the concentration of the sodium hydroxide solution is 0.2 mol / L.

[0071] (2) adding zinc nitrate solution and aluminum nitrate solution into the reaction kettle in sequence, stirring for 30 minutes in a water bath, and then adding sodium hydroxide and sodium bicarbonate mixed solutions respectively, adjusting the pH of the system to 11.3, continuing to stir for 4 hours, standing for 20 hours, and then filtering, washing with clean water until neutral, drying, and crushing to obtain a mixed modified material;

[0072] The drying temperature is 60°C, the drying time is 1 hour, and the concentration of zinc nitrate solution is 1 mol / L;

[0073] The concentration of aluminum nitrate solution is 1.5 mol / L;

[0074] The volume ratio of zinc nitrate solution to aluminum nitrate solution is 1:2;

[0075] The sodium hydroxide concentration in the sodium hydroxide and sodium bicarbonate mixed solution is 0.8 mol / L, and the sodium bicarbonate concentration is 1.5 mol / L.

[0076] (3) adding the mixed modified material to the stacked calcium-based bentonite, mixing evenly, and obtaining a standby material; the mixed modified material and calcium-based bentonite have a mixing mass ratio of 1.5:20.

[0077] (4) Then, the reserved material is placed in a resistance furnace and subjected to a staged calcination treatment to obtain calcined bentonite; the staged calcination treatment is as follows:

[0078] First, calcine at 300°C for 15 minutes, then adjust the temperature to 420°C, and continue calcining for 20 minutes to complete the entire calcination process; the staged calcination process is carried out in an air atmosphere; the heating rate of the staged calcination process is 5°C / s.

[0079] Example 3

[0080] A method for preparing sludge-based pressure-resistant permeable bricks, comprising:

[0081] (1) Weigh the raw materials of each component according to their weight: 35 parts of steel slag, 44 parts of sludge, 14 parts of potassium feldspar, 2.2 parts of calcined modified bentonite, 4 parts of fly ash, and 1.8 parts of perlite powder;

[0082] The weight ratio of the sludge to the calcined modified bentonite is 20:1;

[0083] The calcined modified bentonite is prepared by modifying calcium-based bentonite as a raw material.

[0084] (2) adding each raw material component into a mixer in sequence, and then adding 10% of water to the total amount of the raw materials, continuing to stir, and sealing and aging for 20 hours to obtain an aged material;

[0085] (3) injecting the aged material into a mold, pressing it into a brick at a pressure of 23 MPa, and then drying the brick at 100° C. for 12 hours;

[0086] (4) placing the dried bricks in a furnace and firing them into shape;

[0087] The firing heating rate is 6℃ / min, the temperature is raised to 750℃ and kept for 1h, and then the temperature is further raised to 1110℃ and sintered and kept for 2h, then cooled and discharged.

[0088] The method for preparing calcined modified bentonite comprises the following steps:

[0089] (1) First, the calcium-based bentonite is piled up, and then the sodium hydroxide solution is evenly sprayed until the water content of the calcium-based bentonite reaches 46%, and then the calcium-based bentonite is piled up at room temperature for 24 hours; the concentration of the sodium hydroxide solution is 0.2 mol / L.

[0090] (2) adding zinc nitrate solution and aluminum nitrate solution into the reaction kettle in sequence, stirring for 30 minutes in a water bath, and then adding sodium hydroxide and sodium bicarbonate mixed solutions respectively, adjusting the pH of the system to 11.3, continuing to stir for 4 hours, standing for 20 hours, and then filtering, washing with clean water until neutral, drying, and crushing to obtain a mixed modified material;

[0091] The drying temperature is 60°C, the drying time is 1 hour, and the concentration of zinc nitrate solution is 1 mol / L;

[0092] The concentration of aluminum nitrate solution is 1.5 mol / L;

[0093] The volume ratio of zinc nitrate solution to aluminum nitrate solution is 1:2;

[0094] The sodium hydroxide concentration in the sodium hydroxide and sodium bicarbonate mixed solution is 0.8 mol / L, and the sodium bicarbonate concentration is 1.5 mol / L.

[0095] (3) adding the mixed modified material to the stacked calcium-based bentonite, mixing evenly, and obtaining a standby material; the mixed modified material and calcium-based bentonite have a mixing mass ratio of 1.5:20.

[0096] (4) Then, the reserved material is placed in a resistance furnace and subjected to a staged calcination treatment to obtain calcined bentonite; the staged calcination treatment is as follows:

[0097] First, calcine at 300°C for 15 minutes, then adjust the temperature to 420°C, and continue calcining for 20 minutes to complete the entire calcination process; the staged calcination process is carried out in an air atmosphere; the heating rate of the staged calcination process is 5°C / s.

[0098] Example 4

[0099] A method for preparing sludge-based pressure-resistant permeable bricks, comprising:

[0100] (1) Weigh the raw materials of each component according to their weight: 38 parts of steel slag, 60 parts of sludge, 20 parts of potassium feldspar, 3 parts of calcined modified bentonite, 5 parts of fly ash, and 2 parts of perlite powder;

[0101] The weight ratio of the sludge to the calcined modified bentonite is 20:1;

[0102] The calcined modified bentonite is prepared by modifying calcium-based bentonite as a raw material.

[0103] (2) adding each raw material component into a mixer in sequence, and then adding 10% of water to the total amount of the raw materials, continuing to stir, and sealing and aging for 20 hours to obtain an aged material;

[0104] (3) injecting the aged material into a mold, pressing it into a brick at a pressure of 24 MPa, and then drying the brick at 100° C. for 12 hours;

[0105] (4) placing the dried bricks in a furnace and firing them into shape;

[0106] The firing heating rate is 6℃ / min, the temperature is raised to 750℃ and kept for 1h, and then the temperature is further raised to 1110℃ and sintered and kept for 2h, then cooled and discharged.

[0107] The method for preparing calcined modified bentonite comprises the following steps:

[0108] (1) First, the calcium-based bentonite is piled up, and then the sodium hydroxide solution is evenly sprayed until the water content of the calcium-based bentonite reaches 50%, and then the calcium-based bentonite is piled up at room temperature for 24 hours; the concentration of the sodium hydroxide solution is 0.2 mol / L.

[0109] (2) adding zinc nitrate solution and aluminum nitrate solution into the reaction kettle in sequence, stirring for 30 minutes in a water bath, and then adding sodium hydroxide and sodium bicarbonate mixed solutions respectively, adjusting the pH of the system to 11.3, continuing to stir for 4 hours, standing for 20 hours, and then filtering, washing with clean water until neutral, drying, and crushing to obtain a mixed modified material;

[0110] The drying temperature is 60°C, the drying time is 1 hour, and the concentration of zinc nitrate solution is 1 mol / L;

[0111] The concentration of aluminum nitrate solution is 1.5 mol / L;

[0112] The volume ratio of zinc nitrate solution to aluminum nitrate solution is 1:2;

[0113] The sodium hydroxide concentration in the sodium hydroxide and sodium bicarbonate mixed solution is 0.8 mol / L, and the sodium bicarbonate concentration is 1.5 mol / L.

[0114] (3) adding the mixed modified material to the stacked calcium-based bentonite, mixing evenly, and obtaining a standby material; the mixed modified material and calcium-based bentonite have a mixing mass ratio of 3:20.

[0115] (4) Then, the reserved material is placed in a resistance furnace and subjected to a staged calcination treatment to obtain calcined bentonite; the staged calcination treatment is as follows:

[0116] First, calcine at 300°C for 15 minutes, then adjust the temperature to 420°C, and continue calcining for 20 minutes to complete the entire calcination process; the staged calcination process is carried out in an air atmosphere; the heating rate of the staged calcination process is 5°C / s.

[0117] The following is a comparative example:

[0118] Comparative Example 1:

[0119] A method for preparing sludge-based pressure-resistant permeable bricks, comprising:

[0120] (1) Weigh the raw materials of each component according to their weight: 70 parts of steel slag, 4 parts of sludge, 10 parts of potassium feldspar, 1 part of bentonite, 3 parts of fly ash, and 1 part of perlite powder;

[0121] The weight ratio of the sludge to the calcined modified bentonite is 20:1;

[0122] The bentonite is calcium-based bentonite.

[0123] (2) adding each raw material component into a mixer in sequence, and then adding 10% of water to the total amount of the raw materials, continuing to stir, and sealing and aging for 20 hours to obtain an aged material;

[0124] (3) injecting the aged material into a mold, pressing it into a brick at a pressure of 22 MPa, and then drying the brick at 100° C. for 12 hours;

[0125] (4) placing the dried bricks in a furnace and firing them into shape;

[0126] The firing heating rate is 6℃ / min, the temperature is raised to 750℃ and kept for 1h, and then the temperature is further raised to 1110℃ and sintered and kept for 2h, then cooled and discharged.

[0127] test:

[0128] The water permeability coefficient of the permeable bricks of the embodiment and the comparative example was measured according to the standard method in "Permeable Pavement Bricks and Permeable Road Panels" (GB / T25993-2010);

[0129] Table 1

[0130] Water permeability cm / s Example 1 0.112 Example 2 0.103 Example 3 0.108 Example 4 0.101 Comparative Example 1 0.067

[0131] It can be seen from Table 1 that the permeable bricks prepared by the present invention have a higher water permeability coefficient. The increase in the water permeability coefficient can greatly improve the water permeability of the permeable bricks.

[0132] The compressive strength of the sintered bricks of the embodiments and comparative examples was determined according to the standard method of "Permeable Bricks" (JC / T945-2005);

[0133] Table 2

[0134]

[0135]

[0136] It can be seen from Table 2 that the compressive strength of the permeable brick of the present invention is greatly improved, which is mainly achieved through the promoting effect of the introduced calcined modified bentonite.

[0137] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A sludge-based pressure-resistant permeable brick, characterized in that: The composition includes the following components by weight: 30-38 parts of steel slag, 20-60 parts of sludge, 10-20 parts of potassium feldspar, 1-3 parts of calcined modified bentonite, 3-5 parts of fly ash, and 1-2 parts of perlite powder; The weight ratio of the sludge to the calcined modified bentonite is 20:1; The calcined modified bentonite is prepared by modifying calcium-based bentonite as a raw material.

2. The sludge-based pressure-resistant permeable brick according to claim 1, characterized in that: The method for preparing calcined modified bentonite comprises the following steps: (1) First, the calcium-based bentonite is piled up, and then the sodium hydroxide solution is evenly sprayed until the water content of the calcium-based bentonite reaches 40-50%, and then the calcium-based bentonite is piled up at room temperature for 24 hours; (2) adding zinc nitrate solution and aluminum nitrate solution into the reaction kettle in sequence, stirring for 30 minutes in a water bath, and then adding sodium hydroxide and sodium bicarbonate mixed solutions respectively, adjusting the pH of the system to 11.3, continuing to stir for 4 hours, standing for 20 hours, and then filtering, washing with clean water until neutral, drying, and crushing to obtain a mixed modified material; The drying temperature is 60°C and the drying time is 1 hour; (3) adding the mixed modified material to the stacked calcium-based bentonite, mixing evenly, and obtaining a standby material; (4) Then, the prepared material is placed in a resistance furnace and subjected to a staged calcination treatment to obtain calcined bentonite.

3. The sludge-based pressure-resistant permeable brick according to claim 2, characterized in that: In step (1), the concentration of sodium hydroxide solution is 0.2 mol / L.

4. The sludge-based pressure-resistant permeable brick according to claim 2, characterized in that: The concentration of the zinc nitrate solution in step (2) is 1 mol / L; The concentration of aluminum nitrate solution is 1.5 mol / L; The volume ratio of zinc nitrate solution to aluminum nitrate solution is 1:2; The sodium hydroxide concentration in the sodium hydroxide and sodium bicarbonate mixed solution is 0.8 mol / L, and the sodium bicarbonate concentration is 1.5 mol / L.

5. The sludge-based pressure-resistant permeable brick according to claim 2, characterized in that: In step (3), the mixed modified material and calcium-based bentonite have a mixing mass ratio of 1-3:

20.

6. The sludge-based pressure-resistant permeable brick according to claim 2, characterized in that: The staged calcination process in step (4) is as follows: First, calcine at 300°C for 15 minutes, then adjust the temperature to 420°C, and continue calcining for 20 minutes to complete the entire calcination process.

7. The sludge-based pressure-resistant permeable brick according to claim 6, characterized in that: The staged calcination process is performed in an air atmosphere.

8. The sludge-based pressure-resistant permeable brick according to claim 6, characterized in that: The heating rate of the staged calcination process is 5°C / s.

9. The method for preparing a sludge-based pressure-resistant permeable brick according to claim 1, characterized in that: include: (1) Weighing the raw materials of each component according to their weight parts: steel slag, sludge, potassium feldspar, calcined modified bentonite, fly ash, and perlite powder; (2) adding each raw material component into a mixer in sequence, and then adding 10% of water to the total amount of the raw materials, continuing to stir, and sealing and aging for 20 hours to obtain an aged material; (3) injecting the aged material into a mold, pressing it into a brick at a pressure of 22-24 MPa, and then drying the brick at 100° C. for 12 hours; (4) The dried bricks are placed in a Ma Furnace for firing and molding; the firing heating rate is 6°C / min, the temperature is raised to 750°C and kept for 1 hour, and the temperature is further raised to 1110°C and kept for 2 hours, and then cooled and discharged.